خوارزمية جديدة لتتبع نقطة الاستطاعة الأعظمية في الأنظمة الكهروضوئية بالاعتماد على المنطق الضبابي - مسعود صبيح; نسمت أبو طبق; علي أوغلي (Tishreen University, 2018)
Maximum Power Point Tracking is one of the most important issues which earns the attention of researchers because of the low efficiency and high prices  of the photovoltaic cells. The present paper proposes a new maximum power point tracker (MPPT) algorithm, applied to a photovoltaic system composed of photovoltaic arrays, boost DC-DC converter, and resistive load. The new algorithm based on Fuzzy logic, the rules of Fuzzy logic controller (FLC) are determined depending on the voltage and current deviation. Then, the output signal  is modified according to the power deviation. The simulation has been accomplished in MATLAB/SIMULINK software.   Simulation results compared with those obtained by the conventional perturbation and observation (P&O) algorithm show the effectiveness of the new method during steady-state and varying weather conditions. نالت مسألة  تتبع نقطة الاستطاعة الأعظمية Maximum Power Point Tracking (MPPT) اهتمام  الباحثين نظراً لارتفاع أسعار الخلايا الكهروضوئية و انخفاض مردودها. نقترح في هذا البحث خوارزمية جديدة لتتبع نقطة الاستطاعة الأعظمية لنظام كهروضوئي يتألف من ألواح كهروضوئية، مع مقطع رافع Boost Converter، وحمل أومي. تعتمد الخوارزمية المقترحة على استخدام التغير بالجهد و التغير بالتيار كمتحولات دخل لمتحكم المنطق الضبابي  Fuzzy logic controller (FLC) الذي توضع قواعده بالاعتماد عليهما، ثم إجراء تعديل على إشارة الخرج للمتحكم بالاعتماد على التغير بالاستطاعة. تمت النمذجة و المحاكاة باستخدام برنامج MATLAB/SIMULINK، ثم قمنا بمقارنة النتائج مع النتائج التي حصلنا عليها عند تطبيق خوارزمية الاضطراب و المراقبة Perturb-and-Observe (P&O) الأكثر انتشاراً و تبين لدينا فعالية الخوارزمية المقترحة من أجل شروط مختلفة للإشعاع الشمسي و درجة الحرارة.